The Effect of Water Quality on the Density of Velesunio sp. in the Padi Swamp Waters of Erom Village, Merauke: - Sendy Lely Merly; Eka Dahlia Pahharani; Nova Suryawati Monika; Lindon R Pane; Jeremias Rumala Tuhumena; Ariyati H Fadel (Jurnal Moluska Indonesia, 2026)
Rawa Padi has various types of organism, one of which is the Velesunio sp. (Lea, 1859). As freshwater mussels (Velesunio sp.) are used as a source of food needs by the surrounding community. This study aims to analyze the relationship between the density of Velesunio sp. and the water quality in the Rawa Padi waters. Moreover, water quality can be expressed by water quality parameters including physical and chemical parameters. This study was conducted from July to August in 2023. A survey method with a purposive sampling approach were used in this study. Quadrants measuring 1 x 1 m were spread 30 times at each research station during sampling activities. Furthermore, from total duration of sampling, there were a total of 90 quadrants in all research locations. The results showed that the highest density was at station I in July with a density of 7.40 ind/m²; while, the lowest density was at station I in August with density of 1.50 ind/m². On the other hand, water quality namely pH range about 7.93-8.71, temperature between 270C until 32°C, brightness within 4-96 cm, and depth approximately 0.55-0.79 m. Thus, based on regression analysis, it is known that the water quality parameters that have closest relationship to the density of Velesunio sp. in Rawa Padi waters is brightness. The regression value was R = 0.9077 or 90.77% at Station I, R = 0.9962 or 99.62% at Station II, and R = 0.9941 or 99.41% at Station III.